The influence of natural disasters on violence, mental health, food insecurity, and stunting in the Philippines: Findings from a nationally representative cohort. (September 2021) - Edwards, Ben; Gray, Matthew; Borja, Judith
Abstract: Background: Climate change is leading to an increased number of natural disasters. Children from low- and middle-income countries are disproportionately affected. The impacts of exposure to multiple natural disasters on the development of children are not well understood. The Philippines had 6.5 million people affected by natural disasters in 2018 and is therefore an ideal country in which to study the cumulative effects of natural disasters on human development. Methods: We used wave 1 (2016–17) of the Longitudinal Cohort Study on the Filipino Child, a nationally representative cohort study of 4952 10-year-old children, to examine the impact of natural disasters. For caregivers, we examined mental health, family violence, and food insecurity. For children, we examined exposure to violence and stunting. We used random effects models to estimate the associations between natural disasters and children's development outcomes and caregivers' outcomes, after adjusting for neighbourhood, demographic, and geographic variables. Disaster exposure was measured using caregiver-reported measures of cumulative exposure and cumulative impact of disasters, average neighbourhood reports and data linked from the International Disaster Database (EM-DAT), an independent measure of community exposure to disaster. Findings: We found that experiencing natural disasters, as measured by neighbourhood reports, was associated with higher levels of family violence in the previous 12 months, parenting stress, children witnessing physical violence, physical abuse of children, stunting in children, and greater food insecurity. Associations with individual self-reported exposure showed was similar. Associations with natural disasters measured using EM-DAT data showed a similar pattern: exposure to greater numbers of natural disasters was associated with higher levels of family violence, physical abuse of children, stunting in children, and food insecurity. Impacts of disasters was associated with higher levels of family violence, depression and food insecurity. Interpretation: This is the first national study to document that cumulative measures of natural disasters had small, but wide-ranging, impacts on children and their caregivers. Further research is needed to identify factors that will protect populations who are at risk of high levels of natural disasters to ensure the optimal development of children. Funding: The Philippines Project, The Australian National University. Highlights: The implications of multiple natural disasters for child development are not well understood. First national study on the impact of multiple natural disasters on children. More natural disasters associated with child physical abuse and family violence. Exposure to a greater number of natural disasters associated with stunting and food insecurity. More natural disasters led to worse caregivers' depression and stress.